2009
DOI: 10.4049/jimmunol.0900753
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ Regulatory T Cells Resist a Novel Form of CD28- and Fas-Dependent p53-Induced T Cell Apoptosis

Abstract: Ag receptor stimulation of preactivated T cells causes rapid cell death in an IL-2– and Fas-dependent manner. This phenomenon, known as activation-induced cell death (AICD), plays a pivotal role in the removal of Ag-reactive T cells after initial expansion. In this study, we report a novel form of T cell apoptosis that is distinct from classic AICD. When peripheral T cells were activated with anti-CD3 and anti-CD28 Abs precoated onto plastic plates, CD4+CD25− and CD8 T cells initially expanded but underwent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Thus, a plausible explanation for the lack of AICD in Tregs is diminished or absent CD95L expression. However, contradictory results regarding CD95L expression by Tregs have been obtained (16,(25)(26)(27)) that prompted us to investigate CD95L surface protein expression in Tregs compared with that in Tcons by a highly sensitive flow cytometry protocol. Tcons displayed high CD95L surface protein upon stimulation for 20 h with anti-CD3 Ab on day 6 of in vitro culture and upon P/I treatment on both day 0 (freshly isolated) and day 6 of culture ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a plausible explanation for the lack of AICD in Tregs is diminished or absent CD95L expression. However, contradictory results regarding CD95L expression by Tregs have been obtained (16,(25)(26)(27)) that prompted us to investigate CD95L surface protein expression in Tregs compared with that in Tcons by a highly sensitive flow cytometry protocol. Tcons displayed high CD95L surface protein upon stimulation for 20 h with anti-CD3 Ab on day 6 of in vitro culture and upon P/I treatment on both day 0 (freshly isolated) and day 6 of culture ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon appeared to be independent of p53, although consistently, p53-deficient mice activated T cells were equally sensitive to AIDC as control mice [84]. Singh et al (2010) [85] observed a non-classical process of antigen-induced T cell death in CD4+CD25− and CD8+ T cells by sustained T cell receptor (TCR) stimulation caused by plate-bound anti-CD3/anti-CD28 antibodies (Abs) which is dependent on p53. The last contributes to cell death of CD4+CD25− cells via upregulation of Fas.…”
Section: P53 In Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%
“…The last contributes to cell death of CD4+CD25− cells via upregulation of Fas. Remarkably, naturally occurring FoxP3+ Treg were found resistant to this form of apoptosis undergoing significant expansion upon stimulation [85]. Watanabe et al (2014) [86,87] highlighted, still in a mouse model, that downmodulation of p53 following TCR signaling enforces antigen-specific CD4+ T cell responses while limiting bystander proliferation of non-specific T cells.…”
Section: P53 In Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%
“…The identification and functional characterization of other important subsets of T cells, namely Tregs, T H 17 and NKT cells, has renewed interest in susceptibility to apoptosis as a mechanism of skewing of the immune response. Mouse Tregs have been shown to be highly resistant to FasL-mediated apoptosis, whereas freshly isolated human Tregs were susceptible but became resistant upon stimulation (142)(143)(144)(145). The data on T H 17 cell resistance to apoptosis is relatively sparse.…”
Section: Resistance To Apoptosis Among T-cell Subsetsmentioning
confidence: 99%